Personality and Cognitive Decline in Older Adults: Data From a Longitudinal Sample and Meta-Analysis - Luchetti, Martina (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: Personality traits are associated with risk of dementia; less is known about their association with the trajectory of cognitive functioning. This research examines the association between the 5 major dimensions of personality and cognitive function and decline in older adulthood and includes a meta-analysis of published studies. METHOD: Personality traits, objective and subjective memory, and cognitive status were collected in a large national sample (N = 13,987) with a 4-year follow-up period. For each trait, the meta-analysis pooled results from up to 5 prospective studies to examine personality and change in global cognition. RESULTS: Higher Neuroticism was associated with worse performance on all cognitive measures and greater decline in memory, whereas higher Conscientiousness and Openness were associated with better memory performance concurrently and less decline over time. All traits were associated with subjective memory. Higher Conscientiousness and lower Extraversion were associated with better cognitive status and less decline. Although modest, these associations were generally larger than that of hypertension, diabetes, history of psychological treatment, obesity, smoking, and physical inactivity. The meta-analysis supported the association between Neuroticism and Conscientiousness and cognitive decline. DISCUSSION: Personality is associated with cognitive decline in older adults, with effects comparable to established clinical and lifestyle risk factors.